Comparative analysis of the logistics and sustainability of the ports of Callao and Cartagena de Indias - Boyano-Fram, Teófilo O. (EFIM Ediciones, 2021)
In times of crisis the supply cannot be stopped for food security and business sustainability, the covid and future pandemics will have an impact on the world, but trade relations continue and so does the supply, this article was done by collecting data and references that exist between the two ports in South America and are The Port of Callao in Peru and the Port of Cartagena de Indias in Colombia, we interviewed experts on the subject, reviewing specialized journals and reports that are issued by the entities in charge, was also taken into account: the sustainability of the Ports, its port movement and the port logistics, the intention is to observe its relation that is given between the growth of the Port and the city, in it is concluded that both ports contribute to the economy of the Continent and that they present asymmetries by their georeferentiation and vocation with their economic and social surroundings.